The Effect of MSME Development on GRDP in East Java Post-Pandemi Covid-19 - Wardani, Vindi Kusuma; Nasikh, Nasikh (Bina Bangsa International Journal of Business and Management, 2023)
Micro, Small, and Medium Enterprises (MSMEs) around the world are considered an important segment of any economy. The pandemic that has had an impact on the economic sector has also had an impact on the MSME sector. Economic growth in the regions can be seen from the value of the Gross Regional Domestic Product (GRDP). MSMEs are East Java GRDP boosters. This research was conducted with the aim of knowing the effect of the development of Micro, Small, and Medium Enterprises (MSMEs) on the Gross Regional Domestic Product (GRDP) in East Java after the Covid-19 pandemic. The research method used is descriptive with a quantitative approach. The data analyzed in this study is time series data from the 2016-2020 period obtained from the Central Statistics Agency (BPS) and the MSME Cooperative Office, East Java Province. Data analysis in the study used SPSS 26 for windows. The tests used are the Normality Test and Simple Linear Regression Test. The results obtained in this study are that the number of MSMEs has increased every year, but in 2020 the number of MSMEs decreased from the previous year, namely 1,316,400,000,000.00. The GRDP of East Java Province in 2016-2020 based on constant prices showed a significant increase, but in 2020 the GRDP of East Java Province experienced a contraction compared to the previous year, which was 2,299,460,000,000.00. The results of the Classical Normality Assumption Test show that the processed data is normally distributed. The test results show the sig. (2-tailed) at 0.200 means the sig value > 0.05. The direction of influence of MSMEs on GRDP is positive. The t-test shows the value of t-count > t-table. So it can be concluded that there is a significant influence of MSMEs on the GRDP of East Java Province in 2016-2020 of 100%